Cognitive manipulation of emotional and non-emotional information in working memory of patients with depression: a rigid processing style - Cui, Jiacheng; Wen, Jianglin; Wang, Dong (Frontiers in Psychology, 2023)
Cognitive psychology is one of the important perspectives to understand depression. A large number of scholars have studied the cognitive characteristics of depression and proposed cognitive theoretical hypotheses about depression. Compared with previous studies, recent researchers have increasingly focused on the exploration of the comprehensive cognitive process of patients with depression. The cognitive operation ability of working memory is an important comprehensive cognitive process, which reflects how individuals establish representations and is the basis for the formation of experience and schema. This study aims to explore whether there are abnormalities in the cognitive operation ability of patients with depression. And to analyze its possible role in the pathogenesis and maintenance of depression.